Answer:
The answer to this question can be described as follows:
when x= 2. so, quotient value= 1.12
when x=-2. so, quotient value= 0.04
Explanation:
Given:
![\bold{(x+1)/(x(x-1)) \% (4)/(3)(x-1)} \\](https://img.qammunity.org/2021/formulas/mathematics/college/v347bc2p6phr38qgeidblb1s1ab56ef02l.png)
where,
![x \\eq 0, x\\eq 1 , and \ x\\eq -1](https://img.qammunity.org/2021/formulas/mathematics/college/byk339el5bmhs9elhs961ph2b0bighcyii.png)
In the given question the value of x is not equal to 1, 0, and -1. so, we put the value x= 2 in the above equation:
when x= 2
![\Rightarrow (2+1)/(2(2-1)) \% (4)/(3)(2-1)\\\\\Rightarrow (3)/(2(1)) \% (4)/(3)(1)\\\\\Rightarrow (3)/(2) \% (4)/(3)\\\\\Rightarrow 1.5 \% 1.33\\\\\Rightarrow \boxed{1.12}](https://img.qammunity.org/2021/formulas/mathematics/college/m4rig0mgd7qomggsizlh9p0ozgv3ivz6wo.png)
when we put the value x= -2. it will give:
![\Rightarrow (-2+1)/(-2(-2-1))\ \% (4)/(3)(-2-1)\\\\\Rightarrow (-1)/(-2(-3)) \ \% (4)/(3)(-3)\\\\\Rightarrow (-1)/(6) \ \% -4 \\\\\Rightarrow -0.16\ \% -4 \\\\ \Rightarrow \boxed{0.04}](https://img.qammunity.org/2021/formulas/mathematics/college/az9t454u8bnbhy2j0pwowb2ychjoc9titt.png)